CHARACTERIZATION OF HEAT SHOCK PROTEINS IN BRUCELLA ABORTUS AND INTERACTION OF THESE PROTEINS WITH PATIENT AND CONTROL SERA - R Rajabnia (Babol University of Medical Sciences, 2008)
BACKGROUND AND OBJECTIVE: The bacteria begin to synthesize heat shock proteins (hsp) when facing elevated temperatures. Some of the hsps recognized during infection by host immune system. The goal of this study was to determine the synthetic pattern of hsps in brucella abortus that were subjected to different heat shocks and antigenecity of hsps in both patient and healthy sera by immuno blot assay.METHODS: In this experimental trial study, five brucella abortus were isolated from cows and were subjected to 39, 40, and 42ºC heat shocks. Then cell proteins were extracted and electrophoresis in polyacrylamide gels (SDS-PAGE) was performed. Finally antigenecity of hsps (hsp60) in healthy as well as patient sera were surveyed by immuno blot.FINDINGS: The major protein groups were in the range of 30-75 and 14-20 KDa in SDS-PAGE. The amounts of a 60 KDa protein band (hsp60) was significantly enhanced following heat shock as compared to the unheated cells. The sera from brucella patients reacted with several of these cell derived protein bands in immuno blots, none of which were reactive with sera from healthy individuals. The 60 KDa band was the most significant and showed strong reactions with all brucellosis sera samples. CONCLUSION: This study showed the brucella abortus produces heat shock proteins, especially hsp60, in response to heat shock. Brucellosis patient’s sera reacted strongly with these molecules. This observation points to the antigenecity properties of hsps, specially the overwhelming response to hsp-60. Therefore, probably the hsp60 can be an antigen candidate for ELISA test development as well as for engineering sub unit vaccine against brucella.